2017
DOI: 10.1128/aac.00188-17
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Assessment of the Safety and Effectiveness of the New Tablet and Intravenous Formulations of Posaconazole in the Prophylaxis of Invasive Fungal Infections via Analysis of 343 Courses

Abstract: Posaconazole is the preferred mold-active azole for prophylaxis against invasive fungal infections (IFIs) in patients with hematological malignancy. Delayedrelease tablet and intravenous formulations of posaconazole have recently become available, but clinical data are limited. We sought to examine the real-world pharmacokinetics and prophylactic effectiveness of the new formulations of posaconazole given as prophylaxis for patients with hematological malignancy. A retrospective cohort of all consecutive adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 25 publications
4
42
3
7
Order By: Relevance
“…In addition, we found a positive association between age and POS C min in univariate analyses, which is in accordance with previous studies performed in hematological patients treated with POS-susp (7,17) or POS-tab (18). However, this association did not reach significance in multivariate analyses, suggesting that the influence of age on POS C min was dependent on another variable in our cohort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we found a positive association between age and POS C min in univariate analyses, which is in accordance with previous studies performed in hematological patients treated with POS-susp (7,17) or POS-tab (18). However, this association did not reach significance in multivariate analyses, suggesting that the influence of age on POS C min was dependent on another variable in our cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies reported CVs for the POS-tab C min , but comparing CV values is problematic since calculation methods of CV differ. Here, we used the method described by Bland (21) to calculate within-subject CV, whereas a different approach was used in other studies, i.e., the ratio between standard error and the mean POS C min in each patient (18,22). Finally, as explained above, we adjusted the POS C min for the POS dose in our cohort, which was not done in the other studies (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…20% of these patients developed liver injury, mostly hyperbilirubinemia but this is often multifactorial. More importantly, grade 3‐4 elevations in hepatic enzymes were only observed in 2% of the patients without pre‐existing liver injury with mostly spontaneous resolution despite treatment continuation . Thus, in the current literature, information about the toxicity of high POS serum concentrations is limited but no increase in the number of AEs was observed in patients with higher than average serum concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the upper C min limit that we propose for ISA must be interpreted with caution. Second, we propose upper limits for the POS and ISA C min , above which no gain of efficacy could be expected, but some adverse effects could occur at lower C min values [9,30,31,36]. Anyway, further studies with direct clinical outcomes (efficacy and safety) are required to confirm and validate the interest of such thresholds.…”
Section: Discussionmentioning
confidence: 97%
“…In the phase 3 study of the delayed-release tablet POS, C min from 0.5 to 3.75 mg/L was considered to be safe [1]. Moreover, recent studies failed to demonstrate any link between the POS C min and toxicity [12,14,30], even if some authors reported some cases of adverse events in patients with a POS C min > 1.8 mg/L [9,31,32]. Finally, although our results suggest that a gain of antifungal activity can be expected until a POS C min of 4.8 mg/L, additional research is needed to determine whether such POS exposure significantly improves efficacy without inducing toxicity.…”
Section: Discussionmentioning
confidence: 99%